Perception and attitude toward telemedicine services in Caloocan City, the Philoippines a cross-sectional study - Carandang, Rogie Royce; Sara, James; Pararuan, Kyla; Velasco, Isable Maria; Aquino, Jose Gerardo; Miranda, Kevin Jace (2025)
The telemedicine industry experienced rapid growth during the COVID-19 pandemic, offering
remote healthcare consultations as an alternative to in-person visits. Despite growing interest, the implementation and adaptation of telemedicine services continue to face significant challenges in developing countries like the Philippines. This study aimed to assess public perception and attitude toward telemedicine services to inform strategies for broader adoption and long-term sustainability. A community-based cross-sectional survey was conducted among residents of Caloocan City, the Philippines. Perceptions and attitudes were evaluated using a modified Bloom’s cut-off point, and multiple logistic regression analysis was used to identify factors associated with telemedicine use. Among 438 participants, 224 (51.1%) had an adequate perception of telemedicine, whereas the majority (n = 398, 90.9%) expressed negative attitudes. Findings showed that both adequate perception [adjusted odds ratio (AOR) = 1.38; 95% CI = 1.17–1.61] and positive attitude (AOR = 1.82; 95% CI = 1.58–2.11) were significantly associated with telemedicine utilization. Additional associated factors included being female, possessing a bachelor’s degree or higher, being employed, and reporting excellent self-rated health. These findings provide key insights for enhancing telemedicine uptake and bridging gaps in digital health access in the Philippines.
Keywords: Telemedicine